2020
DOI: 10.1097/fbp.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic operant responses in deer mice (Peromyscus maniculatus bairdii) and its response to outcome manipulation and serotonergic intervention

Abstract: Investigating the motivational triggers underlying naturalistic compulsive-like behavior is generally regarded as challenging. To this extent, the current study aimed to establish a proof-of-concept for future investigation by probing unconditioned and naturalistic operant responses aimed at obtaining nesting material by normal (NNB) and large (LNB) nest building deer mice (Peromyscus maniculatus bairdii). LNB mice and NNB controls were individually placed in cages equipped with a lever-operated nesting materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Escitalopram oxalate [ESC; BLD Pharma ® , Shanghai, China; 50 mg/kg/day; Wolmarans et al ( 2013 )] and LOR [Aspen Pharmacare ® , Qheberha, South Africa; 2 mg/kg/day; Wolmarans et al ( 2022 )] were prepared for sub-acute (8-day) and chronic (35-day) oral administration via the drinking water, respectively. These concentrations were based on the average daily liquid consumption of deer mice [0.25 ml/g/day; Wolmarans et al ( 2013 ) and de Brouwer et al ( 2020 )]. Drug intake was confirmed by means of daily liquid consumption measurements (average liquid intake of mice receiving normal water, escitalopram, and lorazepam was similar across all days of testing; mixed-effects analysis; inter-day effect: F (29,500) = 1.18, p = 0.24; between-exposure effect: F (2,23) = 1.78, p = 0.19; Kruskal-Wallis analysis of the average liquid intake over time per exposure group: p = 0.37; average liquid consumption over all days of testing: 4.1 ml per animal; average escitalopram consumption per day: 0.82 ± 0.2 mg; average lorazepam consumption per day: 0.033 ± 0.008 mg).…”
Section: Methodsmentioning
confidence: 99%
“…Escitalopram oxalate [ESC; BLD Pharma ® , Shanghai, China; 50 mg/kg/day; Wolmarans et al ( 2013 )] and LOR [Aspen Pharmacare ® , Qheberha, South Africa; 2 mg/kg/day; Wolmarans et al ( 2022 )] were prepared for sub-acute (8-day) and chronic (35-day) oral administration via the drinking water, respectively. These concentrations were based on the average daily liquid consumption of deer mice [0.25 ml/g/day; Wolmarans et al ( 2013 ) and de Brouwer et al ( 2020 )]. Drug intake was confirmed by means of daily liquid consumption measurements (average liquid intake of mice receiving normal water, escitalopram, and lorazepam was similar across all days of testing; mixed-effects analysis; inter-day effect: F (29,500) = 1.18, p = 0.24; between-exposure effect: F (2,23) = 1.78, p = 0.19; Kruskal-Wallis analysis of the average liquid intake over time per exposure group: p = 0.37; average liquid consumption over all days of testing: 4.1 ml per animal; average escitalopram consumption per day: 0.82 ± 0.2 mg; average lorazepam consumption per day: 0.033 ± 0.008 mg).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, deer mice drink fluid at an average rate of 0.25 ml/g/24 hr (de Brouwer, Fick, et al., 2020). Although this has not been shown to change as a function of drug exposure or additives added to the drinking water (de Brouwer, Fick, et al., 2020; de Brouwer, Harvey, et al., 2020), the average daily fluid intake per cage was monitored by weighing the residual amount of liquid left on each following day (Supplementary Information). Istradefylline was constituted in concentrations that ensured the delivery of the appropriate doses to animals over a 24‐hr period (4 and 8 mg/100 ml for the 10 and 20 mg kg −1 day −1 doses, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…10,386:2021). The number of animals included in this investigation was broadly based on extensive prior investigation where we showed that at least 30-45% of mice develop LNB [34,[36][37][38][39] and motor stereotypies [40][41][42][43] in adulthood.…”
Section: Study Layoutmentioning
confidence: 99%